2000
DOI: 10.1109/68.867988
|View full text |Cite
|
Sign up to set email alerts
|

Application of modified finite-difference formulas to the analysis of z-variant rib waveguides

Abstract: Abstract-Modified finite-difference formulas for a general position of an interface are applied to the propagating beam analysis of -variant rib waveguides. The modified formula based on the semivectorial H-field is found to be more insensitive to variation in an interface position than that on the E-field. A discretization error is satisfactorily reduced in tilted and tapered rib waveguides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…(17) is approximated in Eqs. (14) and (15) If the refractive index profile is uniform, the improved finite-difference formula coincides with the finitedifference formula derived from the conventional Taylor series expansion. Therefore, the algorithm of the improved finite-difference formula can be used regardless of existence of the refractive index discontinuity.…”
Section: Derivation Of Fourth-order Accurate Improved Finite-differenmentioning
confidence: 91%
See 2 more Smart Citations
“…(17) is approximated in Eqs. (14) and (15) If the refractive index profile is uniform, the improved finite-difference formula coincides with the finitedifference formula derived from the conventional Taylor series expansion. Therefore, the algorithm of the improved finite-difference formula can be used regardless of existence of the refractive index discontinuity.…”
Section: Derivation Of Fourth-order Accurate Improved Finite-differenmentioning
confidence: 91%
“…In the formulation, the alternate direction implicit method (ADIM) is used, resulting in an accurate and fast three-dimensional BPM, while the advantage that the discontinuity position of the refractive index can be chosen arbitrarily is utilized [13,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A full vectorial analysis would require a large computational effort; however, in most devices, the index contrast is only moderately high and a semivectorial approach can be used. As such several semivectorial methods have been developed which are mainly used for modal analysis of devices or for low angle propagation (Stern 1988a,b;Vassallo 1992Vassallo , 1997Kim and Ramaswamy 1989; D. Bhattacharya · A. Sharma (B) Physics Department, Indian Institution of Technology Delhi, New Delhi 110016, India e-mail: asharma@physics.iitd.ac.in Hoekstra et al 1992;Wijnands et al 1995;Yamauchi et al 1997Yamauchi et al , 2000Liu et al 1993;Mitomi and Kasaya 1998). Few semivectorial methods have been used for wide-angle beam propagation but only in devices with low index contrast (Shibayama et al 2006a,b).…”
Section: Introductionmentioning
confidence: 99%
“…The temperatures involved are assumed to be very high so that the radiative heat transfer is significant, which renders the problem highly non-linear even with the assumption of a differential approximation for the radiative heat flux. Yamauchi et al [8] presented modified finite-difference formulas for a general proposition of an interface that they applied to the propagating beam analysis of z-variant rib waveguides. They observed that a discretization error is satisfactorily reduced in tilted and tapered rib waveguides.…”
Section: Introductionmentioning
confidence: 99%